DEKOLORISASI AIR LIMBAH PENGOLAHAN GURITA MENGGUNAKAN METODE AOT(ADVANCE OXIDATION TREATMENT) DENGAN REAGEN FENTON - Ganden Supriyanto; Khoirun Nisak R; Abdulloh Abdulloh (Jurnal Kimia Riset, 2018)
ABSTRACT This research aims to determine the effectiveness of Advance Oxidation Treatment (AOT) method with the use of Fenton reagent in decolorization of octopus canning wastewater’s red colour. The use of Fenton reagent (H2O2 and Fe2+) will produce hydroxyl radicals (∙OH) that will oxidize the red colour so the octopus canning wastewater to be colourless and safe to discharged into the environment. Determination of octopus canning wastewater's decolorization is done by determining the change of red color's intensity using Pt/Co scale. The main parameter in determining the decolorization of octopus canning wastewater using Advanced Oxidation Treatment (AOT) with Fenton reagent are time, concentration of Fe2+, concentration of H2O2, and pH. The maximum decolorization of octopus canning wastewater was reached at following condition rarely 55 minutes, with Fe2+ concentration of 42,86 ppm, H2O2 concentration of 85,71 ppm, and pH 4. With a capacity of red color’s decolorization is 49,08 %. Key words : Advance Oxidation Treatment (AOT), decolorization, Fenton reagent    ABSTRAK Penelitian ini bertujuan untuk mengetahui efektifitas metode Advance Oxidation Treatment  (AOT)  dengan menggunaan reagen Fenton dalam mendekolorisasi warna merah yang terdapat dalam air limbah pengolahan gurita. Penggunaan reagen Fenton (H2O2 dan Fe2+) akan menghasilkan radikal hidroksil (∙OH) yang bisa menghilangkan warna merah yang terdapat di dalam limbah sehingga limbah menjadi tidak berwarna dan aman untuk dibuang ke lingkungan. Penentuan dekolorisasi air limbah pengolahan gurita dilakukan dengan menentukan perubahan intensitas warna merah menggunakan skala Pt/Co. Parameter utama yang digunakan dalam metode Advance Oxidation Treatment  (AOT) adalah waktu, konsentrasi Fe2+, konsentrasi H2O2, dan pH. Hasil optimum dari dekolorisasi air limbah pengolahan gurita adalah pada waktu 55 menit, konsentrasi Fe2+ 42,86 ppm, konsentrasi H2O2 85,71 ppm, dan pH 4. Dengan kapasitas dekolorisasi warna merah sebesar 49,08 %. Kata kunci  : Advance Oxidation Treatment  (AOT), dekolorisasi, reagen Fenton